Pelatihan Mug Ecoprint untuk Meningkatkan Kreativitas Ibu PKK oleh Mahasiswa KKNT Desa Padelegan - Rosyidatul, Fadhila; Rahmawati, Ika Dian; A'yun, Dya Qurotul; Ningsih, Puji Rahayu (Jurnal Solutif: Jurnal Pengabdian Masyarakat, 2025)
Ecoprint is an art technique that uses natural materials, such as leaves, flowers and other parts of plants, to print patterns on fabric or ceramic media. This technique is increasingly popular because apart from producing aesthetic products, it is also environmentally friendly. The potential for ecoprint development in Padelegan Village is very large, considering the abundant natural resources, especially various types of plants that can be used as raw materials for ecoprints. The Ecoprint Mug Training held by Real Work Lecture (KKNT) students in Padelegan Village aims to increase the creativity of PKK mothers by teaching them new skills in making ecoprint mugs. Through this training, PKK women are expected to be able to utilize the potential of the natural surroundings to create products with economic value, increase their creativity, and support family economic empowerment. The methods used in this training include socialization, preparation of tools and materials, and direct practice. The results of the training showed an increase in understanding, skills and creativity of PKK women in making ecoprint mug products that were unique and had the potential to be marketed. This training also has a positive impact on the economic empowerment of village communities by opening business opportunities based on environmentally friendly handicrafts.